ChemInform Abstract: The Photocathodic Properties of a Pb(Zr0.2Ti0.8)O3 Wrapped CaFe2O4 Layer on ITO Coated Quartz for Water Splitting. Issue 32 (12th August 2014) - Cheng, Xiaorong; Chen, Deliang; Dong, Wen; Zheng, Fengang; Fang, Liang; Shen, Mingrong
Abstract: Pb(Zr0.2 Ti0.8 )O3 wrapped CaFe2 O4 particles on indium‐tin oxide (ITO) coated quartz is tested as a photocathode for efficient water splitting.